Compensation, Worklife Balance, Employee Engagement, and Turnover Intention - Ni Nyoman Triningsih; Gede Sri Darma (PT Mattawang Mediatama Solution, 2024)
The significance of conducting this study lies in its pressing relevance to PT Bali Busana Kreasi, aiming to address turnover intention issues and foster a more productive and fulfilling work environment for its employees. The study's core objective is to scrutinize the impact of compensation and work-life balance on turnover intention, with employee engagement serving as a mediating factor. This research employs a quantitative research approach and is conducted at PT Bali Busana Kreasi, situated on Jl Raya Anggi Elok. The data sources encompass both primary and secondary data, with the entire workforce of 162 employees representing the research population. Simple random sampling, employing the Slovin formula, is employed to select 116 samples. The data is analyzed through Structural Equation Modeling.The outcomes of hypothesis testing indicate the following key findings: 1) Compensation exhibits a significant negative influence on turnover. 2) Work-life balance demonstrates a significant negative impact on turnover intention. 3) Compensation positively and significantly affects employee engagement. 4) Work-life balance significantly promotes employee engagement. 5) Employee engagement significantly diminishes turnover intention. 6) compensation mediated by employee engagement on turnover intention has a significant negative effect. 7) there is a significant negative relationship between work-life balance through employee engagement and intention to leave.